(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
This article describes the importance and characteristics of the names of clothing. Clothing terms is an unseperable part of Linguculturology, they also enable to realize cultural sensitivity, historical background and of course It reflects the nation’s religious, profession or purpose according to its look. In this research Environmental adaptability was taken as the main factor of naming the clothes.